145 - PERCEPTION OF THE ACTIVITIES OF THE PSYCHOLOGIST FOR THE HEALTH TEAM OF A HOSPITAL SCHOOL (Fiep Bulletin - online, 2011)
One searches to know the perception of the health professionals of the federal university hospital school concerning the activities of the psychologist who performs in this hospital. A questionnaire was applied covering partner-demographic aspects, professional and the performance of the Psychologist in the hospital. Sixty six professionals of diverse categories of college graduated had participated. The answers to the performance of the Psychologist had been dealt with categorizations using the Microsoft Excel program. The results indicate that the psychologist acts, predominantly, at the professional accompaniment of the staff of the institution; individual psychotherapy attendance; orientation about the difficulties in the work; demands of the interned and related patients; and in the integration between sectors. The importance attributed to its activity is evident, even when taken specifically as individual attendance of the patients and employees. This is further verified when the professionals in the area of humans are compared to those of the area of health. They perceive the action of the Psychologist as more ampler and diversified.
Keywords: Psicologia da Saúde; Psicologia Hospitalar; Atuação do Psicólogo